2018
DOI: 10.1172/jci.insight.122092
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor repertoire features associated with survival in immunotherapy-treated pancreatic ductal adenocarcinoma

Abstract: Research supported by a Stand Up To Cancer Lustgarten Foundation Pancreatic Cancer Convergence Dream Team Translational Research grant (SU2C-AACR-DT14-14). Stand Up To Cancer is a program of the Entertainment Industry Foundation administered by the American Association for Cancer Research (AACR). Additional clinical trial funding was provided by AACR-Pancreatic Cancer Action Network Research Acceleration Network grant (14-90-25-LE), NCI SPORE in GI Cancer (CA062924), Quick-Trials for Novel Cancer Therapies: Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
156
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 22 publications
10
156
0
Order By: Relevance
“…The TCR clonality of both CD4 + and CD8 + T cells is more restricted than in healthy people, and broader T cell responses with greater diversity of CD4 + blood T cell clones may predict the longer survival of patients with melanoma treated with anti‐CTLA4 or PD‐1 antibodies . Many studies have shown that peripheral blood TCR diversity can be used to predict the efficacy of immunotherapy . Therefore, PEG‐rhG‐CSF may improve the efficacy of immunotherapy by increasing peripheral blood TCR diversity; however, further clinical studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The TCR clonality of both CD4 + and CD8 + T cells is more restricted than in healthy people, and broader T cell responses with greater diversity of CD4 + blood T cell clones may predict the longer survival of patients with melanoma treated with anti‐CTLA4 or PD‐1 antibodies . Many studies have shown that peripheral blood TCR diversity can be used to predict the efficacy of immunotherapy . Therefore, PEG‐rhG‐CSF may improve the efficacy of immunotherapy by increasing peripheral blood TCR diversity; however, further clinical studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…19 Many studies have shown that peripheral blood TCR diversity can be used to predict the efficacy of immunotherapy. 17,21,33,34 Therefore, PEG-rhG-CSF may improve the efficacy of immunotherapy by increasing peripheral blood TCR diversity; however, further clinical studies are needed to confirm this. We found no MH overlap on day 3, and day 8-10 showed a significant difference between groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…183,185-187 In several instances, vaccination is further combined with standard treatment regimens including conventional chemotherapy, 117,188-191 radiation therapy, 52,192-195 and targeted anticancer agents, 196-199 or with various immunotherapeutic interventions. 200-205 The latter include (1) immune checkpoint blockers such as the anti-PD-1 mAbs pembrolizumab and nivolumab, 206-208 the anti-PD-L1 mAbs durvalumab and atezolizumab, 209-211 and the anti-CTLA4 mAb ipilimumab; 137,186,212-215 (2) immunostimulatory antibodies such as utomilumab, which stimulates TNF receptor superfamily member 9 (TNFRSF9; best known as 4-1BB or CD137) signaling, 28,216-218 or the CD27 agonist varlilumab; 28,216,219,220 and immunomodulatory agents such as lenalidomide. 221-224 In line with preclinical and clinical data demonstrating that multi-epitope vaccines are generally more powerful than their single-epitope counterparts, 117,225 the most common vaccination strategy employed by these studies consists in targeting simultaneously multiple TAAs (20 studies).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%